Speciation and Risk Characteristics of Heavy Metals in the Sediments of the Yangtze Estuary - Yin, Su; Feng, Cheng-hong; Li, Yang-yang; Yin, Li-feng; Shen, Zhen-yao (Huanjing kexue, 2016)
Based on the investigation on the distribution of total contents and speciation of 8 heavy metals (As, Cd, Cr, Cu, Hg, Ni, Pb, Zn) in the surface sediments at 14 typical sites of the Yangtze Estuary during three hydrological seasons ( wet, normal, and dry seasons) , this study applied equilibrium partitioning approach to build the sediment quality guidelines (SQGs) of the Yangtze Estuary, and assessed ecological risks of the heavy metals. The relationship between ecological risk and speciation of heavy metals was also revealed. The results showed that, except for Cd, the residual fraction was the main speciation of heavy metals, especially for As, Cr and Hg, their residual fraction proportions were all over 90%. The sediment quality guidelines of the Yangtze Estuary for As, Cd, Cr, Cu, Hg, Ni, Pb, Zn were 43.29, 0.672, 79.65, 19.08, 0.569, 339.09, 30.87, 411.36 µg · g⁻¹, respectively. Cu had the highest ecological risk to aquatic organisms. The upstream of Yangtze Estuary was mainly affected by Yangtze River